Assistance in Developing Canvas Model Business Capacity at Walcoo Shoes in Bogor City - Heirunissa, Heirunissa; Bakti, Rizal; Dhamaah, Wahjuny; Eldianson, Rio; Maku, Alin Djafar; Ilham, Anggio (Edumedia Solution, 2025)
MSMEs are an important pillar in the Indonesian economy with a significant contribution to GDP and labor absorption. The fashion industry, especially shoes, is showing strong growth, and WALCOO Shoes as a player in this industry needs to understand and design the right business model. This study aims to analyze the WALCOO Shoes business model using the Business Model Canvas (BMC) approach and SWOT analysis. The SWOT analysis shows that WALCOO Shoes strengths in the comfort and flexibility of its products, but has weaknesses in supporting intensive physical activity and weather resistance. Opportunities include fashion trends and innovative materials, while the main threats come from fierce competition and changing consumer trends. Strategic recommendations for WALCOO Shoes include improving marketing strategies, maintaining product quality, and offering after-sales service with a warranty. The main resources include human resources, raw materials, and sewing machines, while the main activity is the shoemaking process from design to sales. The use of social media and e-commerce such as Tiktok and Shopee is optimized for sales channels. The proposed business model is expected to improve WALCOO Shoes' performance and competitiveness in the shoe industry